P394 Preoperative serum vedolizumab levels do not predict postoperative outcomes in inflammatory bowel disease (IBD). (16th January 2018) - Lopez, N; Zaghiyan, K; Melmed, G; McGovern, D; Jain, A; Targan, S; Fleshner, P; Landers, C
Abstract: Background: It is unknown whether patients with IBD undergoing abdominal surgery after biologic drug exposure are at increased risk of postoperative complications. Prior studies on the association of preoperative vedolizumab (VEDO) therapy use and postoperative outcomes in IBD have been conflicting. Serum levels of anti-TNF drugs are a surrogate for biologic effect on inflammatory mechanisms and have been correlated with postoperative outcomes. In a similar fashion, we sought to clarify associations between serum VEDO levels and postoperative outcomes in IBD. Methods: IBD patients on VEDO, with serum drawn within 7 days before surgery, were identified. Serum VEDO levels were measured by investigators blinded to clinical outcomes using the homogenous mobility shift assay (Prometheus Laboratories Inc.). Patients were divided into 2 groups according to serum levels: Group 1 (undetectable VEDO levels; ≤1.8 μg/ml)) and Group 2 (detectable serum VEDO levels; >1.8 μg/ml). To assess whether a higher level of VEDO affected outcomes, Group 2 was further divided into high and low levels as determined by median detectable serum level. Postoperative outcomes, including the Comprehensive Complication index (CCI)), within 30 days of surgery were collected prospectively. Results: The study cohort of 48 patients had a median age of 31 (range, 14–65) years and included 21 (44%) males. Indications for surgery were ulcerative colitis ( n = 25;52%), Crohn's disease ( n = 20;42%) or indeterminate colitis ( n = 3;6%). Index procedures included subtotal colectomy ( n = 21;44%), small bowel/ileocolic resection ( n = 11; 23%) and ileal pouch-anal anastomoses ( n = 9;19%). Serum VEDO levels were detectable in 30 (63%) patients and not detectable in 18 (38%) patients. Median detectable serum VEDO level at the time of surgery was 8.6 μg/ml (range, 1.9–54.4). Groups 1 and 2 were similar in all preoperative characteristics. There were no significant differences between groups in regards to overall postoperative morbidity (39% vs. 30%; p = 0.54), infectious complications (17% vs. 7%; p = 0.35) or 30-day readmission rates after surgery (22% vs. 13%; p = 0.62), or CCI ( p = 0.35). Fifteen (31%) patients had low detectable levels and 15 (31%) had high detectable levels. There was no association between level of VEDO (high vs. undetectable) and overall postoperative morbidity (39% vs. 20%; p = 0.28), infectious complications (17% vs. 7%; p = 0.61), 30-day readmission rates (22% vs. 13%; p = 0.66) or CCI ( p = 0.11) after surgery. Conclusions: This study showed that the presence and magnitude of serum VEDO levels do not adversely influence postoperative outcomes in IBD patients. Contrary to other studies, there appears to be no deleterious effect of preoperative VEDO use in IBD patients requiring surgery.